1993
DOI: 10.1002/aic.690390910
|View full text |Cite
|
Sign up to set email alerts
|

Transport of gases in miscible polymer blends above and below the glass transition region

Abstract: The study of diffusion and permeation of methane, nitrogen, and helium in miscible blends of poly(styrene-stat-acrylonitrile) (PSAN) and poly(methy1 methacrylate) (PMMA) at 35-140°C shows that permeation coefficients (P) of helium followed the linear logarithmic mixing rule. Positive deviations from the linear logarithmic mixing rule were observed for permeation and diffusion coefficients (0) of methane and nitrogen below the glass transition temperature (Tg). The deviations decreased with increasing temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…For some polymers, Arrhenius plots of the diffusion coefficient present discontinuities in the glass transition region which have been linked to high values of the Δα/α g ratio, where α g is the thermal expansion coefficient at the glassy state and Δα is the change of the thermal expansion coefficient at T g . These discontinuities have not been observed for those polymers in which Δα/α g < 1. Accordingly, whether the values of D evolve smoothly with temperature in the transition from the glassy to the rubbery state depends on the Δα/α g ratio …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For some polymers, Arrhenius plots of the diffusion coefficient present discontinuities in the glass transition region which have been linked to high values of the Δα/α g ratio, where α g is the thermal expansion coefficient at the glassy state and Δα is the change of the thermal expansion coefficient at T g . These discontinuities have not been observed for those polymers in which Δα/α g < 1. Accordingly, whether the values of D evolve smoothly with temperature in the transition from the glassy to the rubbery state depends on the Δα/α g ratio …”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, whether the values of D evolve smoothly with temperature in the transition from the glassy to the rubbery state depends on the ∆R/R g ratio. 43…”
Section: Discussionmentioning
confidence: 99%
“…Hopfenberg and Paul5 reviewed the literature on gas transport in polymer blends and found that the following simple mixing rule for P was useful in the analysis of transport data in blends and copolymers: where ϕ x is the volume fraction of component x and P x is the permeation coefficient. The permeability of homogeneous blends21–23 consisting of miscible polymers approximately obeys the logarithmic rule of mixing, which is derived under the assumption of the additivity of the free volumes of the components. On the other hand, heterogeneous blends are known to show an S‐shape dependence of the logarithm of permeability on the blend composition.…”
Section: Resultsmentioning
confidence: 99%
“…The free volume of natural rubber–cellulose composites at a given temperature and pressure can be written as:42, 43 where υ fA , υ fB , and ϕ A , ϕ B are, respectively, the free volumes and volume fractions of components A (natural rubber) and B (cellulose), respectively, in the mixture, whereas Δυ f is the excess free volume resulting from the mixture of cellulose and natural rubber. By taking into account the mixing rule: where D A and D B are, respectively, the diffusion coefficients of the penetrant in the natural rubber and cellulose phases of the composite.…”
Section: Resultsmentioning
confidence: 99%